2021
DOI: 10.1111/aas.13812
|View full text |Cite
|
Sign up to set email alerts
|

Two‐months quality of life of COVID‐19 invasively ventilated survivors; an Italian single‐center study

Abstract: Background COVID‐19 disease can lead to severe functional impairments after discharge. We assessed the quality of life of invasively ventilated COVID‐19 ARDS survivors. Methods We carried out a prospective follow‐up study of the patients admitted to the Intensive Care Units (ICUs) of a teaching hospital. Patients affected by COVID‐19 ARDS who required invasive ventilation and were successfully discharged home were assessed through the telephone administration of validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 53 publications
5
54
1
2
Order By: Relevance
“…Garrigues et al compared patients managed in hospital wards, with those who were transferred to the ICU, and found that most patients report persistent symptoms after 4 months from hospital discharge, especially fatigue and dyspnea, and except for pain and discomfort, there was no signi cant difference regarding persistent symptoms and HR-QoL between ward and ICU patients [8]. Monti et al performed a 2-months follow-up in a small cohort of 39 consecutive COVID-19 invasively ventilated patients; they found that the overall quality of life was reduced to a similar extent as we found, with cognitive and psychological scales showing no impairment, and the most affected dimensions being self-care, usual activities and pain [47]. In a cohort of 205 mechanically-ventilated critically ill COVID-19 patients from 16 ICUs, the HR-QoL at 90 days after ICU discharge was signi cantly lower than sex and age-matched random sample population not affected by COVID-19 in both physical (mobility, ability to speak, ability to eat) and mental (discomfort, depression, vitality, sexual activity) dimensions [48].…”
Section: Long-term Consequences Of Covid-19supporting
confidence: 67%
“…Garrigues et al compared patients managed in hospital wards, with those who were transferred to the ICU, and found that most patients report persistent symptoms after 4 months from hospital discharge, especially fatigue and dyspnea, and except for pain and discomfort, there was no signi cant difference regarding persistent symptoms and HR-QoL between ward and ICU patients [8]. Monti et al performed a 2-months follow-up in a small cohort of 39 consecutive COVID-19 invasively ventilated patients; they found that the overall quality of life was reduced to a similar extent as we found, with cognitive and psychological scales showing no impairment, and the most affected dimensions being self-care, usual activities and pain [47]. In a cohort of 205 mechanically-ventilated critically ill COVID-19 patients from 16 ICUs, the HR-QoL at 90 days after ICU discharge was signi cantly lower than sex and age-matched random sample population not affected by COVID-19 in both physical (mobility, ability to speak, ability to eat) and mental (discomfort, depression, vitality, sexual activity) dimensions [48].…”
Section: Long-term Consequences Of Covid-19supporting
confidence: 67%
“…The most frequently reported psychiatric deficits were depression and/or anxiety. In total, this was examined in 47 studies ( Al-Aly et al, 2021 , Alemanno et al, 2021 , Boari et al, 2021 , Chen et al, 2020 , Chevinsky et al, 2021 , Daher et al, 2020 , Darley et al, 2021 , Daugherty et al, 2021 , De Lorenzo et al, 2020 , Frontera et al, 2021 , Gennaro et al, 2021 , González et al, 2021 , Halpin et al, 2021 , Huang et al, 2021a , Iqbal et al, 2021 , Lorenzo et al, 2021 , Matalon et al, 2021 , Mattioli et al, 2021 , Mazza et al, 2020 , Mazza et al, 2021 , Méndez et al, 2021 , Monti et al, 2021 , Morin et al, 2021 , Negrini et al, 2021 , Noviello et al, 2021 , Ortelli et al, 2021 , Poyraz et al, 2021 , Romero-Duarte et al, 2021 , Sykes et al, 2021 , Tanriverdi et al, 2021 , Taquet et al, 2021a , Taquet et al, 2021b , Tomasoni et al, 2021 , Townsend et al, 2021 , van den Borst et al, 2020 , Venturelli et al, 2021 , Wang et al, 2020b , Wang et al, 2020c , Whiteside et al, 2021 , Wong et al, 2020 , Wu et al, 2020 , Xiong et al, 2021 , Yuan et al, 2020 , Zhou et al, 2020 , D'Cruz et al, 2021 , de Graaf et al, 2021 , Weerahandi et al, 2021 ). The results range from no indication of depression or anxiety ( Daher et al, 2020 , Zhou et al, 2020 ) to >30% at follow-up ( De Lorenzo et al, 2020 , Frontera et al, 2021 , Iqbal et al, 2...…”
Section: Resultsmentioning
confidence: 99%
“…Different aspects of cognitive decline were examined in 27 studies ( Al-Aly et al, 2021 , Albu et al, 2021 , Alemanno et al, 2021 , Darley et al, 2021 , Daugherty et al, 2021 , de Graaf et al, 2021 , De Lorenzo et al, 2020 , Gautam et al, 2021 , Gennaro et al, 2021 , Halpin et al, 2021 , Lu et al, 2020 , Mattioli et al, 2021 , Mazza et al, 2021 , Mcloughlin et al, 2020 , Méndez et al, 2021 , Miskowiak et al, 2021 , Monti et al, 2021 , Morin et al, 2021 , Negrini et al, 2021 , Ortelli et al, 2021 , Shang et al, 2021 , Sykes et al, 2021 , Taquet et al, 2021b , van den Borst et al, 2020 , Venturelli et al, 2021 , Whiteside et al, 2021 , Zhou et al, 2020 ). The results range from no cognitive impairments at a 4 months follow-up ( Mattioli et al, 2021 ) to a report of 78% of the patients experiencing impaired performance on at least one cognitive domain 3 months after clinical recovery ( Mazza et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Miskowiak and colleagues found an association between cognitive impairments and D-dimer levels during the acute phase of illness [ 12 ], supporting previous studies that use of heparin and tissue plasminogen activator (tPA) may improve outcomes [ 92 , 93 ]. Cognitive recovery varies, with some studies showing significant recovery in the majority of COVID-19 patients at 1 month [ 94 , 95 ], with Rass and colleagues found that 23% of studied patients had cognitive defects (measured by Montreal Cognitive Assessment) at 3-month follow-up. This was increased to 50% among those who had encephalopathy during COVID-19 illness [ 79 ].…”
Section: Main Textmentioning
confidence: 99%